Empowering Student Communication through Oral Presentation: A Quasi-Experimental Study in EFL Microteaching Contexts - Nurjihan; Irmayani, Irmayani (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2025)
This study analyzes the effect of oral presentation strategies on improving students' communication skills and self-confidence in an educational context, using quantitative research techniques. A group of students gave prepared presentations, and their performance was evaluated before and after the intervention. The results of the study show a significant increase in students' confidence when speaking in public, their understanding of the material presented, and their collaborative abilities during the planning and implementation stages of the presentation. There is also evidence that peer feedback and a supportive classroom can help students feel more calm, motivated, and active while they are giving a presentation. These results show how important it is to teach pupils how to give oral presentations in school. This way of learning encourages students to be involved and helps them grow as people, which is becoming more and more important in today's teaching methods. In addition, this study highlights the importance of utilizing technology to improve the quality and effectiveness of student presentations, which provides advantages in various educational contexts. Future research should investigate the long-term impact of this intervention on students' academic progress and career readiness, while considering demographic factors such as socioeconomic status and prior public speaking experience that may influence students' presentation skills. There is also proof that peer feedback and a supportive classroom can help students feel more comfortable, motivated, and engaged while they are presenting a presentation. These statistics indicate how vital it is for schools to teach kids how to speak in front of a group. This type of learning gets students interested and helps them grow as people, which is becoming more and more crucial in how teachers educate these days. This study also gives teachers useful tips on how to help kids improve their communication skills.